2021
DOI: 10.1002/mds.28612
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Architecture in Autosomal Recessive Spastic Ataxia of Charlevoix‐Saguenay (ARSACS): Insights into Disease Pathogenesis and Biomarkers

Abstract: Background Autosomal recessive spastic ataxia of Charlevoix‐Saguenay (ARSACS) causes unique retinal abnormalities, which have not been systematically investigated. Objective To deeply phenotype the retina in ARSACS in order to better understand its pathogenesis and identify potential biomarkers. Methods We evaluated 29 patients with ARSACS, 66 with spinocerebellar ataxia (SCA), 38 with autosomal recessive cerebellar ataxia (ATX), 22 with hereditary spastic paraplegia (SPG), 21 cases of papilledema, and 20 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…However, the further examination of 13 heterozygous carriers revealed that this thickness (115.5 µm) was just below the 119 µm threshold for distinguishing ARSACS from non-ARSACS patients [21]. A recent study suggests that this cut-off should be increased to 121 µm to provide 100% accuracy in diagnosing ARSACS [22].…”
Section: Discussionmentioning
confidence: 92%
“…However, the further examination of 13 heterozygous carriers revealed that this thickness (115.5 µm) was just below the 119 µm threshold for distinguishing ARSACS from non-ARSACS patients [21]. A recent study suggests that this cut-off should be increased to 121 µm to provide 100% accuracy in diagnosing ARSACS [22].…”
Section: Discussionmentioning
confidence: 92%
“…In fact, patients with Spinocerebellar ataxia type 7 show macular dysfunction and morphological retinal alterations 22,56,57 . Importantly, previous studies reported that patients with Spinocerebellar ataxia type 3 also reveal thinning of the NFL, GCL and macula [29][30][31]58 , but whether the retinal function is affected in patients with this disease remained uncovered. We, therefore, sought to evaluate both the anatomy and function of the retina in patients with Spinocerebellar ataxia type 3 and in a transgenic mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, ATXN3 harbors 12 to about 51 CAGs, whereas in patients with Spinocerebellar ataxia type 3 the gene contains an expanded (CAG) n tract that ranges from ~60 to 87 triplets 3,4 . Intermediate length alleles (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) show incomplete penetrance or differential clinical presentation 5 . The length of the ATXN3 expanded CAG repeat correlates directly with phenotypic severity and disease progression rate, and indirectly with the age at onset of the first clinical manifestations [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the retina may be an excellent source of potential surrogate biomarkers in ARSACS, Rezende Filho et al (2021) performed fundoscopy (another simple cost-effective technique) and OCT on patients with ARSACS and other forms of ataxia (spinocerebellar ataxia, autosomal recessive cerebellar ataxia, hereditary spastic paraplegia). The investigated retinal nerve fiber thickening in ARSACS by fundoscopy provided false negative data, suggesting that this method has lower sensitivity than OCT [ 130 ].…”
Section: Arsacs Diagnosis and Potential Therapeuticsmentioning
confidence: 99%
“…All ARSACS patients presented foveal hypoplasia, in addition to other impairments, such as retinal hyperplasia, sawtooth appearance or papillomacular fold. The above results suggest that monitoring neurophysiological abnormalities could yield promising biomarkers for ARSACS diagnosis [ 72 , 130 ], such as nerve conduction or nerve ultrasonography. Nerve enlargement and peripheral demyelination may be useful biomarkers in ARSACS [ 35 , 36 ].…”
Section: Arsacs Diagnosis and Potential Therapeuticsmentioning
confidence: 99%